The role of entrepreneurial activity in economic catch-up. - Zawwar, Imran (Cranfield University, 2017)
According to an estimate, in the year 1820, the difference in per capita income between the richest and the poorest country was no more than 3:1. However, with the industrial revolution, some countries experienced a significant shift in their economic growth and the gap in per capita income between the countries started to widen up. This process resulted in increasing global inequality as some countries progressed rapidly, while others remained behind and could not catch-up with the developed world. Nevertheless, with the increase in productivity given the rapid advances in technology, the developing countries have started to catch-up and most of them are growing faster than their developed counterparts. The process of catching up by the individual countries implies a reduction in the gap in productivity and per capita income with the developed world and collectively if all the countries start to catch-up it is referred to as convergence. The phenomenon of convergence has received much attention in the literature on economic development and the potential causes of convergence have intrigued several debates. The neoclassical growth theory provides the theoretical construct to explain this process of convergence and the role of capital, labour and technology is argued to be fundamental. In this regard, the basic premise of this research is that although technology is an important determinant for economic convergence, it cannot be implemented without the entrepreneurs in the economy. The role of entrepreneurial activity is considered to be significant in economic growth, but it has not been explored in the models of economic convergence. Utilising the GEM data on total entrepreneurial activity this PhD thesis addresses this gap and building on the economic development and entrepreneurial literature it explores the role of entrepreneurial activity in economic convergence under varying business contexts. More importantly, it tries to ascertain what type of entrepreneurial activity assists the catching up countries to progress and reduce their gap in productivity and income with the developed world. As the first step in this research, a systematic review of the literature was conducted resulting in a theoretical framework which uncovered the gaps in the existing knowledge. This informed the respective research questions and provided the design for the empirical research that followed. The first empirical paper showed that the impact of entrepreneurial activity in catching up economies, is only significant in the presence of a feedback loop, i.e. as improved entrepreneurial activity from one year feeds into another, helping the catching up countries to grow faster and reduce the gap in productivity and income with the higher incumbent economies. The second empirical paper showed that in the presence of a feedback loop it is only the opportunity entrepreneurial activity that has a significant impact in reducing the GDP gap, while necessity entrepreneurial activity is insignificant. In a world which is characterised by resource constraints, the biggest public policy issue is effective utilisation of resources. To this end, this research has great insights for public policymakers who are interested in formulating policies for impactful entrepreneurship which can expedite the process of economic development. It shows the importance of entrepreneurial activity in economic catch-up, provides insights into entrepreneurial motivation and at the same time emphasise the value of a feedback loop.
Keywords: Business context; entrepreneurial activity; economic catch-up; convergence; opportunity entrepreneurship; necessity entrepreneurship